The role of inflammation and muscle dedifferentiation in the prognosis of retroperitoneal dedifferentiated liposarcoma - Dorian Yarih Garcia-Ortega; Gabriela Concepción Alamilla-García; Ana Paulina Melendez-Fernandez; Sylvia Veronica Villavicencio-Valencia; Claudia Haydee Sarai Caro-Sanchez; Kuauhyama Luna-Ortiz (Clinical Surgical Oncology)
Introduction: Retroperitoneal liposarcomas (RPLS) is the most prevalent soft tissue sarcomas in this location; dedifferentiated liposarcoma (DDLS) poses significant challenges for treatment due to its aggressive nature and poor prognosis. Myogenic dedifferentiation within DDLS may influence surgical outcomes and patient survival. This study investigates the impact of myogenic dedifferentiation and neutrophil-lymphocyte ratio (NLR) as an inflammatory marker on surgical complications and treatment outcomes in RPLS. Methods: We retrospectively analyzed the medical records of 176 patients diagnosed with retroperitoneal sarcoma from January 1, 2005, to December 31, 2018. Fifty patients with DDLPS met the inclusion criteria. Immunohistochemical analyses for muscle-specific markers identified myogenic dedifferentiation. Patients were grouped based on the presence of myogenic dedifferentiation. Preoperative NLR was calculated, and a receiver operating characteristic (ROC) curve determined the optimal NLR cut-off for stratifying inflammatory profiles. Associations between myogenic dedifferentiation, NLR, surgical complications, and treatment outcomes were analyzed. Results: Patients with myogenic dedifferentiation had significantly higher surgical complication rates and lower overall survival (median OS: 26.6 vs. 40.8 months, p ​< ​0.001). An NLR cut-off of 2.6 (AUC ​= ​0.775, 95% CI: 0.63–0.91) predicted myogenic dedifferentiation with 86.7% sensitivity and 54.6% specificity. Elevated NLR was strongly associated with myogenic dedifferentiation (odds ratio ​= ​7.71, 95% CI: 1.51–39.41, p ​= ​0.014), suggesting a heightened inflammatory response influencing tumor aggressiveness. Conclusion: Myogenic dedifferentiation and elevated NLR are associated with increased surgical complications and poorer prognosis in patients with DDLPS. The strong correlation between high NLR and myogenic dedifferentiation underscores the potential role of inflammation in tumor progression. These findings highlight the need for further research into immunotherapy as a possible treatment option for this patient subset to improve management and outcomes.